Locus of Control and Self-Efficacy Relationship with Medication Adherence in Elderly with Hypertension - Dwi Yuniar Ramadhani; Erna Fitriana; Cicik Dwi Febriyanti (Universitas Nahdlatul Ulama Surabaya, 2022)
Patients with hypertension in the elderly often experience non-compliance in the treatment process. In addition, they also experience difficulty in controlling themselves, which is known as the locus of control. An unhealthy lifestyle in the elderly tends to have low self-efficacy, which has an impact on non-adherence to treatment. Therefore, this study aims to identify the dominant factors associated with medication adherence in the elderly with hypertension. The study design was correlational analytic with a cross sectional approach. The population in this study were 36 elderly people with a diagnosis of hypertension who were selected using a total sampling technique. The questionnaire used a multidimensional Health Locus of Control Scale (MHLCS) form C, Self-efficacy for Managing Hypertension, MMAS-8 (Morisky Medical Adherence Scale-8 Items). Data analysis using Pearson Product Moment static test and Linear Regression. In this study, it was found that locus of control and medication adherence had a significant relationship with p-value=0.005, and r-value =0.460, while self-efficacy and medication adherence had a significant relationship with p-value= 0.001 and r-value= 0.527. The most dominant variable of medication adherence was self-efficacy (p=0.02; B=0.335). Based on these results, it can be concluded that the elderly with hypertension who adhere to medication have a good locus of control and high self-efficacy. Adherence to taking medication can be improved by providing health education and increasing self-efficacy through support from family.